Wersyfikacja w cyklu „Polska” Marcina Świetlickiego - Mastalski, Arkadiusz Sylwester (Zagadnienia Rodzajów Literackich, 2025)
The article will focus on analyzing Marcin Świetlicki’s ars versificatoria in the “Polska” cycle, considering its place in the poet’s oeuvre and possible shifts in poetic idiom. Created from the beginning of the author’s career, this cycle offers insight into certain aspects of his poetic style. I will examine transformations within the cycle, particularly in relation to the poetic subject and literary communication. My approach follows Adam Kulawik’s concept of verse (derived form Shklovsky’s prijom) as a device organizing perception. The analysis will be based on Lucylla Pszczołowska’s criteria: verse structure and meter, its relation to syntax, stanzaic organization, and sound patterns, while also considering contemporary trends in poetic form. As I seek to demonstrate, the author, from the very first poem of the cycle, pursues a carefully conceived poetics, manifested through the deployment and modification of such poetic elements as verse construction, metrical and rhythmic (or deliberately disrupted) patterns, the architecture of supralinear structures and the interrelations between them, as well as the juxtaposition of divergent formal orders. These strategies are closely aligned with the evolving stance of the poetic subject toward a transforming reality — one that is articulated not only within the poetry itself but also underscored in the author’s commentary. By limiting the interpretation primarily to the level of the versification — that is, to what directly emerges from the poem’s formal elements, its structure, and the intertextual relationships among prosodic structures of different poems — I aim to demonstrate how useful these aspects could be in further interpretation of the poet’s oeuvre.